Detailed Geometric and Electronic Structures of a One‐Electron‐Oxidized Ni Salophen Complex and Its Amido Derivatives (Eur. J. Inorg. Chem. 22/2014). Issue 22 (August 2014) - Lecarme, Laureline; Chiang, Linus; Philouze, Christian; Jarjayes, Olivier; Storr, Tim; Thomas, Fabrice
Abstract : The cover picture shows the correlation between the low‐energy near‐infrared absorption spectrum and the spin density in three radical complexes. The crystal structure of one is shown at the bottom right. Mountains that surround the cities of Grenoble and Vancouver fit nicely into the background of the near‐infrared curves. Details are discussed in the article by T. Storr, F. Thomas et al. onp. 3479 ff . For more on the story behind the cover research, see theCover Profile .